Effect of benson relaxation therapy combined with Medical Nutrition Therapy (MNT) on blood sugar levels in patients with type 2 diabetes mellitus - Eka Sutrisna; Yunita Sari; Kamalia Pohan; Nanda Fitria; Rizky Mauliza; Suriani Suriani (AcTion: Aceh Nutrition Journal, 2025)
Type 2 diabetes mellitus is a chronic disease with an increasing global prevalence. Non-pharmacological approaches that may support glycemic control include Benson relaxation therapy, which focuses on stress management, and Medical Nutrition Therapy (MNT), which encompasses nutrition diagnosis, therapy, and counseling. This study aimed to analyze the effects of combining Benson relaxation therapy and MNT on blood glucose levels in patients with type 2 diabetes mellitus. Methods: A quantitative study with a quasi-experimental pretest–posttest two-group design was conducted in the North Aceh District in 2024. A total of 100 respondents participated: 50 individuals in the intervention group and 50 in the control group. The intervention consisted of daily 20-minute Benson relaxation sessions combined with MNT over a 14-day period. Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0,05. Results: The mean blood glucose level in the intervention group decreased from 349,04 ± 16,40 mg/dL at baseline to 299,12 ± 23,89 mg/dL post-intervention (p = 0,001). In contrast, the control group showed an increase from 312,88 ± 19,28 mg/dL to 331,10 ± 16,74 mg/dL (p= 0,042). In conclusion, the combination of Benson relaxation therapy and MNT effectively reduced blood glucose levels in patients with type 2 diabetes mellitus and is recommended as a complementary non-pharmacological therapy.